2018
DOI: 10.1021/acs.cgd.8b01161
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Study on the Effect of Thermodynamic Inhibitors during Methane Hydrate Formation in the Presence of NaCl

Abstract: In this study, we investigate the morphology of methane hydrate formation and growth in the presence of wellknown thermodynamic inhibitors, monoethylene glycol (MEG) and methanol (MeOH) in a quiescent system. Morphology changes observed during the growth of methane hydrate while employing 5 wt % MEG and MeOH solutions in the presence and absence of NaCl are presented. When 5 wt % of MEG or MeOH was present in an aqueous solution individually, hydrate grew predominantly within the bulk solution featuring a "rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
(88 reference statements)
2
14
0
Order By: Relevance
“…The surface roughness of the hydrates varies considerably among the inhibitors used, as well as the degree of translucency. Several authors have reported the increase in surface roughness with the addition of KHIs, as well as with THIs . Classical KHIs such as polyvinylpyrrolidone (PVP), polyvinylcaprolactam (PVCap), and other lactam ring‐containing polymers form rough hydrate films with ridges or wrinkles on methane, tetrahydrofuran (THF), and gas mixtures …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness of the hydrates varies considerably among the inhibitors used, as well as the degree of translucency. Several authors have reported the increase in surface roughness with the addition of KHIs, as well as with THIs . Classical KHIs such as polyvinylpyrrolidone (PVP), polyvinylcaprolactam (PVCap), and other lactam ring‐containing polymers form rough hydrate films with ridges or wrinkles on methane, tetrahydrofuran (THF), and gas mixtures …”
Section: Resultsmentioning
confidence: 99%
“…This dependence of the crystal habit on subcooling, namely the density of grains, ridges, and dendrites, has been reported for several KHIs and THIs, although the particular morphologies are different in each case . Since crystal habit changes to yield morphologies with the lowest energies, these differences can be seen as the system's response to the presence of KHI.…”
Section: Resultsmentioning
confidence: 99%
“…The thermodynamic inhibitors prevent hydrate formation by shifting pressure and temperature to values at which hydrants are unstable. There are several traditional THIs, namely, alcohols (e.g., methanol), electrolytes (e.g., NaCl), and ethylene glycols 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…There are several traditional THIs, namely, alcohols (e.g., methanol), electrolytes (e.g., NaCl), and ethylene glycols. 18,19 As high concentrations of the thermodynamic inhibitor agents (10-50 wt%) must be utilized, the gas hydrate prevention unit may be costly. Methanol injection costs more than $500 million annually to avoid hydrate formation.…”
Section: Introductionmentioning
confidence: 99%
“…formation process through the ring-structure connected in chains, during which water molecules convert to the hydrate crystal structure, while simultaneously decelerating the growth of hydrates by adhering to growth points after hydrates are formed (Kim et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%